Energy efficient clustering for wireless sensor networks. Issue 4 (28th October 2014) - Aliouat, Zibouda; Harous, Saad
Abstract : Purpose: – The purpose of this paper is to design a hierarchical routing protocol. Wireless sensor network (WSN) consists of a set of miniature sensor nodes powered by a low-capacity energy battery. This limitation requires that energy is used in an efficient way and kept as long as possible to allow the WSN to accomplish its mission. Thus, energy conservation is a very important problem facing researchers in this context. Because sending and receiving messages is the activity that consumes the most energy in a WSN, so when designing routing protocols, this problem is targeted specifically. The aim of this paper is to propose a solution to this problem by designing a hierarchical routing protocol. Design/methodology/approach: – The authors started by designing a protocol called efficient energy-aware distributed clustering (EEADC). Simulation result showed EEADC might generate clusters with very small or very large size. To solve this problem, the authors designed a new algorithm called fixed efficient energy-aware distributed clustering (FEEADC). They concluded from the simulation result that cluster-heads (CHs) far away from the base station die faster than the ones closer to it. To remedy this problem, they propose multi-hop fixed efficient energy-aware distributed clustering (M-FEEADC). It is based on a new fixed clustering mechanism, which aims to create a balanced distribution of CHs. It uses data aggregation and sleep/wakeup techniques. Findings: – The simulation results show a significant improvement in terms of energy consumption and network lifetime over the well-known low-energy adaptive clustering hierarchy and threshold-sensitive energy-efficient protocols. Originality/value: – The authors propose M-FEEADC. It is based on a new fixed clustering mechanism, which aims to create a balanced distribution of CHs. It uses data aggregation and sleep/wakeup techniques.